ACLY facilitates alanine flux in the livers of db/db mice: a hyperpolarized [1-13C]pyruvate MRS study - Choi, Young-Suk; Song, Jae Eun; Lim, Seo-Hyun; Song, Ho-Taek (Frontiers in Endocrinology, 2025)
IntroductionNon-alcoholic fatty liver disease (NAFLD) and type 2 diabetes mellitus (T2DM) feature paradoxical increases in both gluconeogenesis and lipogenesis. ATP citrate lyase (ACLY) supports both processes by generating cytosolic acetyl-CoA and oxaloacetate from citrate. While ACLY’s role in lipogenesis is well established, its involvement in amino acid–driven gluconeogenesis remains unclear.MethodsUsing hyperpolarized [1-13C]pyruvate magnetic resonance spectroscopy (MRS), we observed [1-13C]alanine labeling in the livers of db/db mice. To test the effect of ACLY inhibition, mice were treated with BMS-303141, and blood glucose responses, hyperpolarized alanine labeling, and aminotransferase activity were evaluated. Western blotting was performed to assess ACLY phosphorylation.ResultsHyperpolarized alanine labeling was markedly elevated in db/db livers, reflecting enhanced transamination capacity. Pharmacologic ACLY inhibition attenuated alanine- and glutamine-induced hyperglycemia and normalized alanine labeling within 2–4 h, without altering aminotransferase gene expression. These in vivo changes correlated with increased hepatic ACLY phosphorylation and ex vivo ALT assay results.DiscussionTogether, these findings support a model in which ACLY facilitates amino acid–driven gluconeogenesis through metabolic control of ALT-mediated transamination, consistent with increased pyruvate–alanine exchange. Hyperpolarized [1-13C]pyruvate MRS thereby provides a sensitive, translational readout of dynamic hepatic metabolism relevant to NAFLD and T2DM.